Development of a selective CDK7 covalent inhibitor reveals predominant cell cycle phenotype - Olson, Calla M. (Cell Chem Biol, 2019)
Cyclin-dependent kinase 7 (CDK7) regulates both cell cycle and transcription, but its precise role remains elusive. We previously described THZ1, a CDK7 inhibitor, which dramatically inhibits super-enhancer associated gene expression. However, potent CDK12/13 off-target activity obscured CDK7s contribution to this phenotype. Here, we describe the discovery of a highly selective, covalent CDK7 inhibitor. YKL-5-124 causes arrest at the G1/S transition and inhibition of E2F-driven gene expression; these effects are rescued by a CDK7 mutant unable to covalently engage YKL-5-124, demonstrating on-target specificity. Unlike THZ1, treatment with YKL-5-124 resulted in no change to Pol II CTD phosphorylation; however, inhibition could be reconstituted by combining YKL-5-124 and THZ531, a selective CDK12/13 inhibitor, revealing potential redundancies in CDK control of gene transcription. These findings highlight the importance of CDK7/12/13 polypharmacology for anti-cancer activity of THZ1 and posit that selective inhibition of CDK7 may be useful for treatment of cancers marked by E2F misregulation.